MENDORONG PERUBAHAN PERILAKU REMAJA DAN SOSIALISASI EKONOMI KREATIF DI MASA PANDEMI COVID 19 - JOSITA NOVIANA,; SIGIT MURYANTO, (KRIDA CENDEKIA, 2022)
Boyolali University (UBY) has the task and function of implementing the Tri Dharma of Higher Education. Tri Darma is the obligation of universities to organize education, research and community service. Community service consists of various kinds, including Real Work Lectures (KKN). KKN is a manifestation of the practice of learning activities in the context of applying interdisciplinary knowledge which is carried out by students directly in the community. The implementation of the 2022 Community Service Program which will be held from February 1 to March 8, 2022 at Duku Kebonso Rt01/Rw03, Pulisen, Boyolali. The work programs implemented include counseling on the impact of juvenile delinquency and socialization of the creative economy to home-based MSME owners. With the implementation of this Community Service, it is hoped that it will increase the knowledge and insight of the residents of Hamlet Kebonso Rt01/Rw03, Pulisen Village, Boyolali District, Boyolali Regency since the midst of the Covid 19 pandemic which is limiting people's movement space at this time.